1989
DOI: 10.3109/00016488909127545
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Concentration in Saliva along the Time Course of Experimental Coriolis Sickness

Abstract: Procedures designed to evaluate the severity of motion sickness have included subjective reporting of changes in salivation. In order to increase objectivity, we studied the sodium concentration of saliva, which is directly related to the flow rate. Healthy adults with normal vestibular function underwent a modified Coriolis Sickness Susceptibility Index (CSSI) test, utilizing a staircase profile. Saliva was collected without interrupting the stimulus by means of cotton placed beneath the subject's tongue for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…One such classically-defined response is a change in salivation and salivary amylase levels (Gordon et al, 1994; Igarashi et al, 1989; Igarashi et al, 1993). Although most studies described increased salivation prior to emesis, others reported a decrease in salivation (Gordon et al, 1988; Hatcher et al, 1923).…”
Section: Prodromal Physiological Changes: Potential Physiological mentioning
confidence: 99%
“…One such classically-defined response is a change in salivation and salivary amylase levels (Gordon et al, 1994; Igarashi et al, 1989; Igarashi et al, 1993). Although most studies described increased salivation prior to emesis, others reported a decrease in salivation (Gordon et al, 1988; Hatcher et al, 1923).…”
Section: Prodromal Physiological Changes: Potential Physiological mentioning
confidence: 99%